Search 73,207 tutors
FIND TUTORS
Ask a question

Answers by Ayanaw H.

|x+3|-3 > 1 Two case by replacing equal sign, a related equation. Case one x+3 -3-1 = 0 X-1 =0 X = 1 Case two -(x+3)-3-1 =0 -x -3-4 =0 -x-7 =0 -x = 7 x = -7 using a number line analysis: Check each interval (- infinity, -7], [-7, 1] and [1,...

Sol/   use a partial fractions to rewrite F(s)in a form.    Please carefully watch the parentheses  3s/(s^2-s-6) = 3s/(s-3)(s+2) = A/(s-3) + B/(s+2) = (A(s+2)+B(s-2))/((s-3)(s+2)) Therefore we have  A(s+2) +B(s-3)  = 3s plugging...

To solve any math question, there may be more than one ways to solve it. 1.79 by 10.5, multiple both of them by 100 which give us 179 by 1050 and then divide it, 179/1050 = 0.17047---

Which question is right  (2y)^3+(6y)^2    or 2y^3+6y^2 ? To factor this (2y)^3+(6y)^2 =  2^3 y^3+3^2 2^2 y^2 =  2^2 y^2 (2y+3^2 ) =  4y^2 (2y+9) 2y^3 +6y^2 answered by Nataliya